Perches and elevated platforms in commercial broiler farms: use and effect on walking ability, incidence of tibial dyschondroplasia and bone mineral content. (7th November 2016) - Kaukonen, E.; Norring, M.; Valros, A.
Abstract : Modern fast-growing broilers spend excessive periods resting and their activity further decreases with age. Inactivity has been suggested to increase impaired gait and the incidence of leg disorders. Tibial dyschondroplasia (TD) is a common leg pathology in broilers. A more complex environment might facilitate more activity and improve leg health. Perches or elevated platforms bring variety to broilers' environment and could motivate more locomotion. This study examined the impact of perches and elevated platforms on walking ability, the occurrence of TD and level of bone ash and mineral contents. The investigation was performed on four commercial broiler farms throughout six consecutive batches with platforms and four to five with perches. On each farm at least two separate houses were included, enabling the comparison of furnished flocks to control flocks during each batch. Plastic slats with ramp access elevated by 30 cm or wooden perches of 10 and 30 cm height were offered in the furnished house. Farmers recorded the platform and perch usage twice a week with a five-point scale. Gait was scored before slaughter on a six-point scale according to the Welfare Quality ® assessment protocol for poultry. The severity of TD was determined using a four-point scale on farm from all birds gait scored as 3 and at slaughter from 200 birds/flock. Farmers estimated 50% to 100% of the platforms to be occupied in all flocks throughout the entire growing period. Only single birds were perching, thus perch structures were constantly evaluated to be empty. Due to the low use, the perch-equipped houses were excluded when analysing bone content, walking ability and TD. On average, 30% of the tested birds exhibited gait score ⩾3. Younger scoring age resulted in a lower mean gait score and a lower percentage of scores 3 and 4 to 5. Overall, 2.3% of the birds examined at slaughter and 3.5% of the birds with gait score 3 were affected by TD. Leg health was better in birds with access to platforms: mean gait score, the percentage of birds scoring 3, and TD percentage and severity were lower in birds in platform-equipped houses. Elevated structures such as platforms, offering additional possibilities for locomotion to broilers seem to improve their leg health.